Transitions to Adulthood Through Recession Youth and Inequality in a European Comparative Perspective (Taylor & Francis, 2018)
Long-running trends towards increasing inequality between the rich and poor across Europe have been exacerbated by the 2008 global financial crisis and its aftermath. As employment opportunities for young people diminish and as the welfare state is pulled back, pathways to adulthood change and become more difficult to navigate.Transitions to Adulthood Through Recession consists of a collection of papers by researchers from Britain, Norway, Germany, Portugal, Italy and Greece, locating young people's transitions to adulthood in their national social, economic and political contexts. It explores young adulthood with reference to generational continuity and change and intergenerational support. With a cross-national comparative framework, this volume highlights the importance of variations in structural contexts for young people's transitions. Bringing together authors across sub-disciplines such as the sociology of youth, family and kinship, class and inequality and life-course studies, Transitions to Adulthood Through Recession will appeal to academic social scientists as well as final-year undergraduate and postgraduate students interested in fields such as political science, sociology, youth studies, social policy, anthropology and psychology; and a wider public readership.
English
Keywords: Society & culture: general; Sociology; Fiona Devine; Ann Nilsen; transition to adulthood; social inequality; youth research; lifecourse; intergenerational transmission; capital; class; spatial; local; kinship; community; Julia Brannen; Patrick Heady; Sarah Irwin; Abigail Knight; Siyka Kovacheva; Robert MacDonald; Ken Roberts; Tracy Shildrick; Kristoffer Chelsom Vogt